Arms of mercy - Reid, Ruth ([Nashville, Tennessee] : Thomas Nelson, 2018)
"Ruth Reid continues her Amish Mercies series with Arms of Mercy, exploring the question of what do you do when all hope seems lost. On the eve of a new year, Catherine Glick is expecting Zach, her beau of five years, to propose, but instead, the unexpected arrival of an old boyfriend, Elijah Graber, causes her life to spiral out of control. Acting nothing like herself, she proposes marriage to Zach. But he is not only unreceptive, he's upset by her boldness-by her desperation. Disheartened by his rejection, Catherine leaves for Florida to work in her cousin's bakery. Elijah Graber knows that he hurt Catherine when he left their Amish district six years ago, and he's come back to explain his actions-even if it means following her to Florida to do so. He sets out to win her trust and hopefully her heart back on the two-day bus journey from northern Michigan to Florida. Just when Elijah is starting to tear down the walls around Catherine, the bus skids on the icy road and crashes into another bus. In the following mayhem, Elijah is separated from Catherine and forced to go to a hospital to recuperate. As the news of the bus accident becomes ever more tragic and Elijah still hasn't heard word from Catherine, everyone around him gently encourages him to prepare for the worst. But Elijah knows that his hope comes from the Lord, and he will not give up his search for Catherine. He lost her once to a rash decision; he will not lose her again. With supernatural nudging from a red-headed man, Elijah's determined to find Catherine, no matter the cost"--Provided by publisher
Keywords: Amish -- Fiction; Love stories